O projeto de encarceramento em massa no Brasil e seu reflexo no sistema prisional feminino: composições da violência institucional no século XXI (2000-2016) - Martinez, Camila Striato (2024)
This research aims to analyze the political and social factors that led to mass incarceration in Brazil in the first decades of the 21st century and how it affected the female prison system. This process is seen as an intentional project, which resulted in the maintenance of marginalization and criminalization of women of specific social classes and races. Within this goal, there is a need to explore some related issues, such as identifying the social profile of incarcerated women in the country, the current state of the prison system and the Brazilian penal execution process. It was possible to note how central the Lei de Tráfico de Drogas (Drug Trafficking Law) (nº 11.343/06) was as a toll for mass incarceration, and, therefore, it was necessary to assess legislative aspects and law enforcement mechanisms as part of the war on drugs policy. The sources of this research vary: bibliographic studies, official Federal Government documents and reports, laws (such as the Penal Execution Law), documents produced by civil society groups and movements – such as the ITTC and Pastoral Carcerária – as well as interviews with women who have been part of or are knowledgeable of the prison system